Hubungan Kontrol Diri Dengan Perilaku Agresif Siswa Kelas XI Di SMK Negeri 3 Padang - Alya Rahael Permata; Linda Fitria; Indra Wijaya (Yayasan Citra Dharma Cindekia, 2024)
Self-control is the ability an individual has to control himself, both in behavior, thinking, emotions and in making decisions. This research aims to determine the magnitude of the relationship between self-control and students' aggressive behavior. The method used in this research is quantitative with the type of research being correlational. The research was conducted at SMK Negeri 3 Padang class XI. The population of this study was 464 people with a sample of 215 for the 2024/2025 academic year. The sampling technique used was purposive sampling technique. The instrument in this research is a Likert scale questionnaire. Data analysis was carried out using statistical programs on the IBM Statistics 29 computer and Microsoft Excel. Based on the results of data processing, the rcount value was obtained, namely 0.407, while the rtable value was 0.138, because the rcount value was greater than the rtable value (0.407>0.138), it was concluded that there was a positive and significant relationship between self-control and students' aggressive behavior.